Occlusion of Bilobulated Left Atrial Appendage Using the Dual-Watchman Technique: A Long-Term Follow-Up Study - Chen, Tao; Wang, Qing-song; Liu, Ge; Lu, Xu; Song, Ting-ting; Shi, Ming-yuan; Zhu, Hang; Mu, Yang; Guo, Jun; Chen, Yun-dai (Frontiers in Cardiovascular Medicine, 2022)
Background Percutaneous left atrial appendage (LAA) occlusion has been considered an efficient alternative to oral anticoagulation to prevent embolic events in patients with non-valvular atrial fibrillation (NVAF). Due to the complexities and heterogeneous anatomy of the LAA structure, the single-device approach may not always fit a large bilobulated LAA. This study aimed to evaluate the feasibility and safety of one-stop dual Watchman implantation for patients with bilobulated LAA. Methods Included in the analysis were patients who underwent complete LAA closure with dual Watchman devices between December 2015 and December 2021. The anatomic morphology, procedure characteristics, procedure safety, and procedural complications were analyzed. Cardiac CT or transesophageal ultrasound was obtained at 7 days, 6 months, 1 year, and 2 years post-operatively to evaluate the effect of occlusion. Results Among the 330 patients who underwent LAA occlusion during the study period, 7 (2.1%) patients were occluded with one-stop implantation of the double Watchman strategy. Successful occlusion was achieved in all patients. One patient had the double-access sheath strategy for implantation, and 6 patients had only a single-access sheath strategy for implantation. Pericardial effusion occurred in one case during the 7-day perioperative period. There was no device embolization, thrombosis, or obvious peridevice leakage (≥l mm) during the 2-year follow-up, with the exception of two cases with 2 mm of incomplete LAA sealing. Conclusion The one-stop implantation of a dual Watchman is feasible and safe and might provide a strategy to occlude a large bilobulated LAA when incomplete closure is inevitable with a single device.